Rappresentazioni Sociali e decostruzione pedagogica. Analisi dello stigma nell'ambito della salute mentale - Carlo Orefice (Firenze University Press, 2013)
Starting from a perspective that considers relationship between the individual, the social and the media system as closely interconnected and interactive, we want to check out how, in building collective forms of knowledge and their pedagogical deconstruction, representations of mental suffering have a strategic importance in guiding beliefs and operational strategies of care professionals and of those who daily face it, working with and for it. According to the Author in fact, thinking about the construction / deconstruction of the stigma in the field of mental health, provides a useful "model" teaching to understand, and bring out, the implicit and the ideological substrates that operate in an unconscious way in the complexity of pedagogical sciences.